1996
DOI: 10.1128/mcb.16.3.914
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Transcription Terminator of the Procyclin PARP A Unit of Trypanosoma brucei

Abstract: The polycistronic procyclin PARP (for procyclic acidic repetitive protein) A transcription unit of Trypanosoma brucei was completely characterized by the mapping of the termination region. In addition to the tandem of procyclin genes and GRESAG 2.1, this 7.5-to 9.5-kb unit contained another gene for a putative surface protein, termed PAG (for procyclin-associated gene) 3. The terminal 3-kb sequence did not contain significant open reading frames and cross-hybridized with the beginning of one or several transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In L. tarentolae, SL RNA is most probably transcribed by pol II (62). Most aspects of pol II transcription in trypanosomatids are poorly understood, and little is known about how pol II transcription terminates in trypanosomatids (6,39) and other organisms (64). However, termination of small RNA gene transcription is controlled by a well-defined 3Ј box (64).…”
Section: Discussionmentioning
confidence: 99%
“…In L. tarentolae, SL RNA is most probably transcribed by pol II (62). Most aspects of pol II transcription in trypanosomatids are poorly understood, and little is known about how pol II transcription terminates in trypanosomatids (6,39) and other organisms (64). However, termination of small RNA gene transcription is controlled by a well-defined 3Ј box (64).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of miRNA hairpins have been found in clusters of multiple identical copies. The target proteins, 20S proteosome, GM6, and GRESAG 4.2 corresponding to these clustered miRNAs, play essential role in trypanosomiasis (Berberof et al 1996;To and Wang 1997). These miRNAs can act as genetic switches modulating host-parasite interaction and provide useful clue toward control of trypanosomiasis (Mallick et al 2008).…”
Section: Mirnas In Protozoan Parasitesmentioning
confidence: 98%
“…There are several expression site‐associated genes ( ESAG s; reviewed by Pays and Nolan, 1998) between the promoter and the VSG gene, which is the last gene in the transcription unit. In contrast, the procyclin expression sites are short transcription units, previously estimated to be 6–9 kb in length (Rudenko et al ., 1990; Berberof et al ., 1991; 1996; Koenig‐Martin et al ., 1992), that are located internally on chromosomes VI and X (Melville et al ., 1998). Each expression site starts with two or three procyclin genes followed by a procyclin‐associated gene ( PAG; reviewed by Roditi et al ., 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The ends of these transcription units have not been determined. Sequences have been identified that attenuate transcription from the GPEET/PAG3 expression site on chromosome VI (Berberof et al ., 1996); these appear to bind a protein factor (Berberof et al ., 2000). A gene encoding a microtubule‐associated repetitive protein (MARP) is part of a Pol II transcription unit upstream of the EP/PAG1 expression site (Koenig et al ., 1989), but no Pol II attenuator or terminator sequences have been identified between the MARP gene and the procyclin promoter.…”
Section: Introductionmentioning
confidence: 99%